2021
DOI: 10.1161/hypertensionaha.120.16611
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Short-Term Fine Particulate Matter Exposure on Blood Pressure Were Modified by Control Status and Treatment in Hypertensive Patients

Abstract: Previous studies revealed that fine particulate matter (PM 2.5 ) exposure adversely affected blood pressure (BP), but factors that might attenuate this association were still unclear. Using a multicenter panel study among 277 hypertensive participants with intermediate-to-high risk of cardiovascular disease from 4 cities in China, we aimed to explore whether BP control status and antihypertensive medications were potential modifying factors. Each participant carried personal-portable mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Our findings were consistently in agreement with previous studies that also examined the acute exposure effect of BC on BP [38,42,50,[56][57][58][59][60][61][62]. For example, the 7-day cumulative exposure to ambient BC and its positive effect on SBP and DBP findings from our study of traffic enforcers were supported by those from an aging cohort study of older men [38,50], a cohort of participants with metabolic syndrome [42], a panel study of subjects with Type 2 diabetes mellitus [58], and a study on hypertensive patients [62]. In addition, our results of null associations between a 10-h cumulative exposure window to ambient BC and both SBP and DBP were comparable to a cross-over study of women [57] and a cohort of community dwellers living near major highways [56].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistently in agreement with previous studies that also examined the acute exposure effect of BC on BP [38,42,50,[56][57][58][59][60][61][62]. For example, the 7-day cumulative exposure to ambient BC and its positive effect on SBP and DBP findings from our study of traffic enforcers were supported by those from an aging cohort study of older men [38,50], a cohort of participants with metabolic syndrome [42], a panel study of subjects with Type 2 diabetes mellitus [58], and a study on hypertensive patients [62]. In addition, our results of null associations between a 10-h cumulative exposure window to ambient BC and both SBP and DBP were comparable to a cross-over study of women [57] and a cohort of community dwellers living near major highways [56].…”
Section: Discussionsupporting
confidence: 93%
“…A number of observational studies, mainly panel studies, have demonstrated significant associations of short-term PM exposure with changes in a wide range of subclinical outcomes, including fractional exhaled nitric oxide, lung function, blood pressure, heart rate variability (HRV), renal function, and various biomarkers in biospecimens of healthy adults, 20 , 21 , 22 , 23 older individuals, 24 children, 25 and cardiopulmonary disease patients. 26 , 27 , 28 , 29 , 30 , 31 , 32 Moreover, several short-term intervention studies suggested that reducing air pollution exposure by personal protective measures (air purifiers and particulate-filtering respirators) or air quality improvement actions can help alleviate various subclinical effects induced by PM exposure. 33 , 34 , 35 , 36 , 37 Apparent heterogeneity was observed for these findings, probably due to the vast differences in study designs, characteristics of air pollution mixture, population susceptibility, sample size, exposure assessment, outcome measurements (e.g., laboratory tests), statistical models, and covariates adjustment.…”
Section: Epidemiological Evidence On Health Impacts Of Particulates I...mentioning
confidence: 99%
“…Compared with those whose blood pressure control met the appropriate standards, the results of a multi-city panel study among high-risk groups of patients with cardiovascular disease showed that the enhanced short-term exposure to PM 2.5 was associated with an elevation of blood pressure and heart rate variability. [15][16][17] A panel study of healthy adults in Beijing proved that short-term exposure to PM 2.5 might lead to high-density lipoprotein cholesterol dysfunction, an increase in oxidized low-density lipoprotein cholesterol, and an increase in the levels of molecular markers for atherosclerotic plaque rupture and inflammation. [18] Furthermore, a panel study of healthy adults in Shanghai also showed that short-term exposure to PM 2.5 and PM 2.5 constituents (SO 4 2À , Cl À , and K + ) was positively correlated with the levels of molecular markers for systemic inflammation such as tumor necrosis factor-a, interleukin-8, and monocyte chemoattractant protein-1.…”
Section: Mortality Of Cardiovascular Diseasementioning
confidence: 99%